Race, cultural, psychology and law/edited by Kimberly Holt Barrett and - Barrett, Kimberly Holt (ed.) (New Delhi, 2005)
This book was developed to fill a critical void in the field of psychology as it intersects with the legal profession and the justice system of the United States. We each began working with the courts several years ago because of particular professional skills and personal background characteristics Kimberly Barrett entered this domain for several reasons, such as her language proficiency in Spanish, the university courses she taught on race and culture, her research on racism and racial identity, and her professional skills in working with ethnic minority individuals and families, William George entered this domain because of his expertise in teaching about race and minority mental health, his professional experience in corrections, and his research expertise about cross-cultural issues and alcohol involvement in sexual vio lence. Our personal background as a mixed racial couple and parents of multiracial children has also been a source of insight in our thinking about race and society. The chapters are divided into six distinct but overlapping sections. The first section. Race and Justice, considers a range of background, philosophical, and general issues characterizing the interface of race, culture, and the American justice system. The sec ond section focuses on the use of evaluation and assessment procedures for legal pro ceedings. The third section is devoted specifically to immigration issues and topics. The fourth and fifth sections address matters related specifically to working with children. families, and juveniles, including understanding racial and cultural identity processes. The final section focuses on violence victimization, particularly domestic violence and sexual violence. Collectively the coverage explores minority versus majority percep tions of justice, documents racial injustice and cultural disparities, identifies contem porary legal challenges and dilemmas, highlights critical service needs, and describes assessment and treatment procedures. The coverage also presents the background of the law and legal circumstances that surround particular sorts of cases-for example, deportation, asylum, human trafficking, and unaccompanied minors. History is also a cross-cutting theme that radiates throughout the chapters: Knowledge about the back ground and history of particular groups at the hands of our society and its legal institu tions is important for fully appreciating the current plight and dynamics of people caught in the web of American law.
Keywords: Discrimination-Law and legislation-United states